Staff Capabilities And Technological Integration Dictate Vocational Educational Resource Quality: Kemampuan Staf Dan Integrasi Teknologi Menentukan Kualitas Sumber Daya Pendidikan Kejuruan - Syari Nur Zahro; Isna Fitria Agustina; Rury Hilda Pandu Winata; Siti Devi Kurniawati; Nur Arivah Endah Prastiwi; Dimas Maldini Kastellino Putra (Proceedings of The ICECRS, 2025)
General Background Vocational school libraries function as critical knowledge repositories requiring continuous adaptation to complex digital demands to support modern educational processes. Specific Background In Indonesia, these facilities frequently struggle with severe personnel shortages, inadequate staff qualifications, and suboptimal technology implementation. Knowledge Gap While digital automation presents operational solutions, the specific interplay between personnel technical competencies, institutional leadership support, and technology acceptance in vocational settings remains underexplored. Aims This qualitative case study analyzes how personnel capacities determine library employee performance at SMK Negeri 2 Buduran. Results Data from semi-structured interviews, participant observations, and document analysis reveal that service quality depends on complex interactions between staff information technology competencies, library automation system utilization, and strong institutional leadership support. Limited personnel numbers often cause severe fatigue, but adequate training in digital management and automation significantly optimizes operational efficiency. Novelty This research integrates Human Capital theory with the Technology Acceptance Model to map the specific operational dependencies within vocational school library management. Implications Educational institutions must prioritize personnel technology training, allocate adequate budgets for automation, and expand external collaborations to maintain relevant and dynamic learning resources in the digital era. Highlights: Complex interactions connecting human resources with institutional leadership govern operational outcomes. Adequate training regarding computerized management resolves severe administrative workforce shortages. Budget allocations from management directly regulate employee motivation alongside facility modernization. Keywords: Human Resources, Library Management, Employee Performance, Vocational Schools, Information Technology